Pengaruh Kualitas Produk, Harga, Relationship Marketing terhadap Keputusan Pembelian Produk di PT Asaba Pekanbaru - Onny Setiawan; Elsa Serepina Simorangkir; Astri Ayu Purwati (Management Studies and Entrepreneurship Journal (MSEJ), 2020)
Competition in PT ASABA the tight with the globalization which led to the emergence of free trade that makespeople began to think a selective and smart in choosing a product. One of his products office stationary (ATK) is growing. The purpose of research which is to know and analyse the influence of the relationship marketing of purchasing decision of the product in PT ASABA Pekanbaru.The method used is the analysis of the regression linier risks. The sample which was used as much as 260 respondents consisting of a retail and wholesale. This research result indicates that the quality of the products, prices and relationship marketing have a significant effect on the purchasing decision of the product at PT ASABA Pekanbaru. Keywords : Product Quality, Price, Relationship Marketing, Purchasing Decision